“O que é ruim para o aposentado é a falta de reconhecimento do que você foi”: as repercussões da aposentadoria na subjetividade de desembargadores inativos - SOARES, Caroline Serra (2018)
The present research had as general objective to analyze the repercussions of the retirement in the subjectivity of the inactive judge. In order to do so, it was investigated the meanings of work and retirement for inactive lawyers, as well as elements that constitute a source of pleasure and suffering for inactive lawyers, identifying the reasons why the inactive judges returned or not to work. Aiming at the achievement of these objectives, it was chosen as theoretical reference the Psychodynamics of Work in articulation with Historical-Dialectical Materialism. From this perspective, the study consisted in a bibliographical and an empirical research with nine retired judges. It is a qualitative study that had as a data collection instrument a semi-structured interview and for data analysis was used from the Critical Discourse Analysis (ACD, in Portuguese) from Fairclough. It was found that work occupied a central and fundamental place in the lives of the interviewees, when they were in the position in question, especially in the aspect of personal fulfillment and the direction of routine. Besides, the existence of some peculiarities of the position of judge, made the bond even stronger and more complex between the participants and the work. It was concluded that the experience of the retirement process caused a rupture in the constitution of the subjectivity of the interviewees, requiring new modes of subjectivation from the place of inactivity. Given this scenario, it was inferred that the main triggering factor of psychic suffering for the participants in the retirement was the lack of social recognition. Therefore, subjective losses and distress were also experienced by the judges, although they are retired holders of very comfortable financial conditions for the society's standards. Added to this, the speeches of the inactive judges reflected well the various faces of retirement as they experienced from the pleasure of free time, freedom, to feelings of worthlessness, social isolation. It is also added that the reports of the interviewees ratified that work and retirement are two interrelated constructs, since the more the work is important for the life of the individual, the more suffered is their distance from work.